STUDENTS’ ANXIETY FACTORS IN SPEAKING ENGLISH - Supriyani Supriyani; Fitriani Dwi kartikasari (STIBA IEC JAKARTA, 2022)
This research aims to determine the factors that cause second year students’ anxiety when speaking English. It was done in SMPN 3 Kroya Indramayu academic year 2020/2021.The researchers find some problems in speaking skill of second year students are low and do not have enough self-confidence. The problems are influenced by some factors such as teacher, teaching lesson, and students. It makes the researchers interested in conducting research. This research focuses on student’s speaking anxiety based on the characteristics of anxiety and the factors that caused student anxious. This research was qualitative in nature. Data collecting technique was done by observation, interview, and documentation. The research subject was second year student that the number was 64 students. The subject interview of this research was conducted by purposive sampling technique. The subject of research was taken six students from 64 students of 8th B grade. Then it was analyzed by using data reduction, data display, and conclusion drawing/verification. The result of this research shows that students who feel anxiety when speaking English were caused by some factors. Those are classroom activities, ways of teaching, teaching lesson, disbelief in speaking and stressful speaking experiences.